Generation of monoclonal antibodies against native viral proteins using antigen-expressing mammalian cells for mouse immunization - Rose, Natalie; Pinho-Nascimento, Carlos Augusto; Ruggieri, Alessia; Favuzza, Paola; Tamborrini, Marco; Roth, Hanna; Baroni de Moraes, Marcia Terezinha; Matile, Hugues; Jänisch, Thomas; Pluschke, Gerd; Röltgen, Katharina (BMC biotechnology, 2016)
Due to their rising incidence and progressive geographical spread, infections with mosquito-borne viruses, such as dengue (DENV), chikungunya and zika virus, have developed into major public health challenges. Since all of these viruses may cause similar symptoms and can occur in concurrent epidemics, tools for their differential diagnosis and epidemiological monitoring are of urgent need.
Gesehen am 05.05.2020